2004
DOI: 10.1038/sj.sc.3101683
|View full text |Cite
|
Sign up to set email alerts
|

Participation and satisfaction after spinal cord injury: results of a vocational and leisure outcome study

Abstract: Participation and satisfaction after spinal cord injury Schonherr, Marleen C.; Groothoff, J.W.; Mulder, GA; Eisma, WH; Schönherr, M.C. Take-down policy If you believe that this document breaches copyright please contact us providing details, and we will remove access to the work immediately and investigate your claim.Downloaded from the University of Groningen/UMCG research database (Pure): http://www.rug.nl/research/portal. For technical reasons the number of authors shown on this cover page is limited to 10 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
67
3
4

Year Published

2008
2008
2017
2017

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 101 publications
(75 citation statements)
references
References 23 publications
1
67
3
4
Order By: Relevance
“…4,5 In fact, the majority of people with SCI report a high level of life satisfaction, 6 with research indicating that life satisfaction is directly related to involvement in productive activities, such as employment and leisure pursuits. 7 Qualitative studies highlight the importance of meaningful relationships, responsibility, a sense of control over one's own life and engagement in meaningful activity in increasing the individual's QOL. 8 Psychological problems (for example, depression and anxiety) following SCI also appear to be related to individual appraisals and coping responses rather than level of injury or functional impairment.…”
Section: Introductionmentioning
confidence: 99%
“…4,5 In fact, the majority of people with SCI report a high level of life satisfaction, 6 with research indicating that life satisfaction is directly related to involvement in productive activities, such as employment and leisure pursuits. 7 Qualitative studies highlight the importance of meaningful relationships, responsibility, a sense of control over one's own life and engagement in meaningful activity in increasing the individual's QOL. 8 Psychological problems (for example, depression and anxiety) following SCI also appear to be related to individual appraisals and coping responses rather than level of injury or functional impairment.…”
Section: Introductionmentioning
confidence: 99%
“…Physical, attitudinal and psychological obstacles, such as unaffordable equipment, no personal assistance, lack of personal motivation, fear of injury and feeling uncomfortable in socializing with able-bodied individuals, may reduce opportunities for sports activities and decrease the maintenance and growth of relationships after SCI. [9][10][11][12] The correlation among these aspects is not simple to investigate because 'participation' is a complex concept that includes a variety of outdoor activities, such as 'attendance of friends, relatives or colleagues during free time'; 'changing hobbies'; 'time spent outside the home'; 'practicing sports'; 'changes in vocational situation'; 13 and a range of psychological consequences, such as 'involvement in personal relationships'; 'changes in family situation'; 'happiness regarding the quality of sex life'; 'personal autonomy' and 'car driving' . 11 The purpose of this study was to investigate the changes in participation, aimed at the attendance of friends/relatives/colleagues, car driving, hobby and sports activities of people after SCI and their impact on perceived QoL.…”
Section: Introductionmentioning
confidence: 99%
“…In Tasiemski et al 10 sport participation and employment declined after injury due to reduced access to facilities, whereas in a separate study work and leisure time was found to reduce by 40% compared to preinjury status. 11 Access to employment has been recognized as particularly weak within the community for people with SCI. Furthermore, outpatients report a lack of informational support for them to pursue a specific job they had re-trained for and were provided with information for a more 'suitable' placement.…”
Section: Introductionmentioning
confidence: 99%